Single‐Atomic Site Catalyst with Heme Enzymes‐Like Active Sites for Electrochemical Sensing of Hydrogen Peroxide. Issue 25 (24th May 2021) - Ding, Shichao; Lyu, Zhaoyuan; Fang, Lingzhe; Li, Tao; Zhu, Wenlei; Li, Suiqiong; Li, Xin; Li, Jin‐Cheng; Du, Dan; Lin, Yuehe
Abstract: Heme enzymes, with the pentacoordinate heme iron active sites, possess high catalytic activity and selectivity in biosensing applications. However, they are still subject to limited catalytic stability in the complex environment and high cost for broad applications in electrochemical sensing. It is meaningful to develop a novel substitute that has a similar structure to some heme enzymes and mimics their enzyme activities. One emerging strategy is to design the Fe‐N‐C based single‐atomic site catalysts (SASCs). The obtained atomically dispersed Fe‐Nx active sites can mimic the active sites of heme enzymes effectively. In this work, a SASC (Fe‐SASC/NW) is synthesized by doping single iron atoms in polypyrrole (PPy) derived carbon nanowire via a zinc‐atom‐assisted method. The proposed Fe‐SASC/NW shows high heme enzyme‐like catalytic performance for hydrogen peroxide (H2 O2 ) with a specific activity of 42.8 U mg −1 . An electrochemical sensor based on Fe‐SASC/NW is developed for the detection of H2 O2 . This sensor exhibits a wide detection concentration range from 5.0 × 10 −10 m to 0.5 m and an excellent limit of detection (LOD) of 46.35 × 10 −9 m . Such excellent catalytic activity and electrochemical sensing sensitivity are attributed to the isolated Fe‐Nx active sites and their structural similarity with natural metalloproteases. Abstract : A Fe‐based single‐atomic site catalyst nanowire (Fe‐SASC/NW) is synthesized by doping single iron atoms in polypyrrole (PPy) derived carbon nanowires. The atomically dispersed Fe‐Nx active sites in the proposed Fe‐SASC/NW can mimic the natural metalloproteases active sites and show high heme enzyme‐like catalytic performance. The electrochemical sensor based on Fe‐SASC/NW exhibits excellent electrochemical sensing sensitivity and potential practical application prospects.